Asian Development Review. - Sawada, Yasuyuki (Asian development review, 2021)
Other articles explore social capital and innovation in East Asia, poverty trends in South Asia, and country-specific specific studies in Indonesia and Thailand. Also presented is an analysis of the relationship between government intervention, institutional quality, and income equality in selected economies in Asia and the Pacific from 1988 to 2014.